Building Community Capacity for Harm Reduction: An Adaptive Implementation Science Approach in Rural Appalachian Ohio. - Sibley, Adams L.; Schalkoff, Christine A.; Colston, David C.; Piscalko, Hannah M.; Spears, Abby G.; Miller, William C.; Go, Vivian F. (Substance Use: Research & Treatment, 2026)
Background: Rural communities face significant implementation challenges addressing the overdose epidemic, including limited treatment capacity, pervasive stigma toward people who use drugs, and social and political opposition to evidence-based interventions. Objectives: Rather than implementing prescribed harm reduction services that may face community resistance, the Ohio Opioid Project adopted a capacity-building approach to address structural barriers and enhance community readiness for future harm reduction and treatment innovation across 3 rural Appalachian Ohio counties. Methods: This applied implementation project used the Evidence-Making Intervention framework with process evaluation. Mixed-methods formative research included interviews with stakeholders (n = 34) and people who use drugs (n = 30), respondent-driven sampling surveys with people who use drugs (n = 258), organizational network analysis, and surveillance data review. A 9-member Community Leadership Board – including health commissioners, treatment providers, and harm reduction program representatives – co-developed interventions targeting 3 structural barriers: substance use-related stigma, interagency fragmentation, and inadequate provider capacity. Community members served as leadership board representatives, implementation staff, intervention consultants, and data collectors, democratizing research involvement and building local public health capacity. Implementation followed an adaptive approach, allowing activities to evolve based on emerging needs, policy changes, and the COVID-19 pandemic. Results: The service delivery plan included 20+ activities across stigma reduction, interagency coordination, and provider capacity building. Key activities included peer recovery supporter training, law enforcement harm reduction seminars, faith-based stigma reduction forums, conflict resolution processes, establishment of drug court buprenorphine protocols, and HCV telehealth partnerships. Multiple activities were sustained by community partners beyond the research period, including resource clearinghouses, new regional partnerships, and organizational protocols integrating harm reduction into existing services. Conclusions: Capacity-building implementation science can address structural barriers to community-based harm reduction in resistant rural settings. By prioritizing community co-creation and adaptive implementation, this approach created foundational conditions for sustainable harm reduction innovation while respecting local contexts and readiness for change.